ALCOHOL AND AL LAW REGIME - E. Utyashov (Гуманитарные и юридические исследования)
The article deals with topical issues of legal regulation of alcohol turnover in the conditions of martial law. The current legislation of Russia and a number of former Soviet countries regulating the procedure for the introduction and implementation of this legal regime contains a provision on special turnover of alcoholic beverages on the list of measures. To date, Russia has developed both an official and unofficial market for the production of alcohol and its consumption, and a certain balance has been formed between the amount of alcohol produced and its sales, which is unlikely to be changed by limiting its production or consumption without financial, economic and social consequences. A possible ban on official production and its implementation will provoke an increase in moonshine and other negative consequences, which are demonstrated in the article. This conclusion raises the question of whether it is appropriate to include on the list of events held under martial law "a special regime of alcohol trafficking", as it does not reflect not only the objective realities of the current state of affairs, but also the experience of the historical past of Russia and a number of other European countries. Within the framework of the current legal regulation, there are enough flexible and effective measures aimed at limiting the use of alcoholic beverages, which do not need to be fixed in the relevant Federal constitutional law. A comparative analysis of similar legislation in European countries does not contain such restrictions. A historical study of restrictions on the turnover of alcoholic beverages during the First World War showed both positive and, to a greater extent, its negative consequences for Russia. The legal regulation of alcohol consumption during the Second World War is fundamentally different from the restrictions that took place in the period 1914-1918. The state took into account mistakes and their consequences for society and the army and avoided the introduction of "prohibition" during the war. Areas of public relations for which the alcohol ban has had a positive effect are demonstrated. The negative results of restricting the turnover of alcoholic beverages for the economy and social sphere, both in conditions of martial law and in peacetime, are revealed. Conclusions are formulated about the inexpediency of the ban on alcohol trafficking in the conditions of the martial law regime.